A rationale for targeting the P2X7 receptor in Coronavirus disease 19 - Di Virgilio, Francesco; Tang, Yong; Sarti, Alba Clara; Rossato, Marco (British journal of pharmacology, 2020)
Severe pneumonia which shares several of the features of acute respiratory distress syndrome (ARDS) is the main cause of morbidity and mortality in Coronavirus disease 19 (Covid‐19) for which there is no effective treatment, so far. ARDS is caused and sustained by an uncontrolled inflammatory activation characterized by a massive release of cytokines (cytokine storm), diffuse lung oedema, inflammatory cell infiltration, and disseminated coagulation. Macrophage and T lymphocyte dysfunction plays a central role in this syndrome. In several experimental in vitro and in vivo models, many of these pathophysiological changes are triggered by stimulation of the P2X7 receptor. We hypothesize that this receptor might be an ideal candidate to target in Covid‐19‐associated severe pneumonia. Linked Articles This article is part of a themed issue on The Pharmacology of COVID‐19. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v177.21/issuetoc